Influence of Loans on Total Assets, Return on Equity, and Inflation on Islamic Banks’ Capital Buffer - Elfa Duwina; Any Eliza; Nur Wahyu Ningsih (Mutanaqishah: Journal of Islamic Banking, 2026)
Purpose – This study aims to examine the influence of Loans to Total Assets (LOTA), Return on Equity (ROE), and Inflation on the Capital Buffer Methodology – This study employs a quantitative approach, utilizing a causal associative study and multiple linear regression as its analytical methods. The data used are secondary data sourced from Islamic banking statistics for the period from January 2020 to December 2024. The analytical tool used in this study is Eviews 10. Findings – The results show that Loans to Total Assets (LOTA) has no significant effect on the Capital Buffer. Return on Equity (ROE) has no significant effect on the Capital Buffer. Inflation has no significant effect on the Capital Buffer. Implications – The results of this study provide recommendations for each bank. They can be used by bank management to inform decisions on asset and capital management strategies to maintain financial stability amid fluctuating inflation. Originality – Providing insight into the importance of financial management, this research is original because it combines factors that have not been widely discussed in the context of Islamic banks in Indonesia, thereby making a new contribution to the literature and practice of the Islamic banking industry.